2015
DOI: 10.1371/journal.pone.0130794
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Runoff Hydrograph on Soil Surfaces with Different Microtopography Using a Travel Time Method at the Plot Scale

Abstract: In this study, a simple travel time-based runoff model was proposed to simulate a runoff hydrograph on soil surfaces with different microtopographies. Three main parameters, i.e., rainfall intensity (I), mean flow velocity (v m) and ponding time of depression (t p), were inputted into this model. The soil surface was divided into numerous grid cells, and the flow length of each grid cell (l i) was then calculated from a digital elevation model (DEM). The flow velocity in each grid cell (v i) was derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These differences in summits and depressions lead to different microrelief responses to rainfall erosion processes in both space and time. Zhao and Wu () simulated the runoff hydrograph on the surface with mounds and depressions using a travel‐time method, and their results suggested that microrelief has a significant effect on the surface flow path and hence affects the total runoff and sediment yields.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in summits and depressions lead to different microrelief responses to rainfall erosion processes in both space and time. Zhao and Wu () simulated the runoff hydrograph on the surface with mounds and depressions using a travel‐time method, and their results suggested that microrelief has a significant effect on the surface flow path and hence affects the total runoff and sediment yields.…”
Section: Discussionmentioning
confidence: 99%
“…Physically based hydrological models (e.g., Brunner and Simmons, 2012;Ameli and Creed, 2017) have not yet been integrated into our framework. However, fill-and-spill is a complex and spatially distributed hydrological process highly affected by many factors, such as surface topography, surface roughness, soil infiltration, soil properties, depression storage, precipitation, evapotranspiration, snowmelt runoff, and groundwater exchange (Tromp-van Meerveld and McDonnell, 2006a, b;Zhao and Wu, 2015;Evenson et al, 2016;Hayashi et al, 2016). Nevertheless, our study presents the first attempt to use lidar data for deriving nested wetland catchments and simulating flow paths in the broadscale Pipestem subbasin in the PPR.…”
Section: Discussionmentioning
confidence: 99%
“…In general, cells with high flow accumulation values correspond to areas of concentrated flow (e.g. stream channels), while cells with a flow accumulation value of zero correspond to the pattern of ridges (Zhu, 2016). Therefore, flow accumulation provides a basis for identifying ridgelines and delineating catchment boundaries.…”
Section: Delineation Of Nested Wetland Catchmentsmentioning
confidence: 99%
“…Physically based hydrological models (e.g., Brunner and Simmons, 2012;Ameli and Creed, 2017) have not yet been integrated into our framework. However, fill-and-spill is a complex and spatially distributed hydrological process highly affected by many factors, such as surface topography, surface roughness, soil infiltration, soil properties, depression storage, precipitation, evapotranspiration, snowmelt runoff, and groundwater exchange (Tromp-van Meerveld and McDonnell, 2006a, b;Evenson et al, 2015;Zhao and Wu, 2015;Evenson et al, 2016;Hayashi et al, 2016). Nevertheless, our study presents the first attempt to use lidar data for deriving nested wetland catchments and simulating flow paths in the broad-scale Pipestem subbasin in the PPR.…”
Section: Discussionmentioning
confidence: 99%